NEXUS BETWEEN GROWTH AND HUMAN DEVELOPMENT INDEX: EVIDENCE FROM INDIA AND INDIAN STATES - Bhowmik, Dr. Dinesh (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
In this paper, the author endeavors to show the nature of HDI and the relation between HDI of India and economic growth, rate of unemployment, GDP and GDP per capita respectively during 1990-2016. The author used semi-log and double log regression model and also used Bai-Perron Model (2003) for structural breaks, Granger model (1969) for causality, Johansen model (1988,1996) for cointegration and vector error correction and Sala-i-Martin(1996) model for convergence test in the Indian States. The paper concludes that the HDI of India has been increasing at a rate of 1.55% per year from 1990 to 2016.HDI has three upward structural breaks in 1996, 2004 and 2011 respectively. HDI of India does not follow a random walk hypothesis. One percent increase in HDI of India led to 1.41% increase in growth rate per year during 1990-2016. This relationship is co-integrated and they have no bidirectional causality. Their VECM is unstable and non-stationary and error correction is significant and fast for equation ∆log(GDP growth rate). Moreover, one percent rise in HDI per year led to 5.86% rise in GDP, 4.828 % increase in GDP per capita and 0.5028% decrease in unemployment rate per year respectively during 1990-2016 in India. There is a positive association between HDI, GSDP, and GSDP per capita of all states in 1983, 1987-88, 1999-00, 2004-05, 2009-10 and 2011-12. These relationships are valid for high plus medium human development and low human development states of India for those years. In Fixed effect model of panel data, the regression between of all states’ HDI and GSDP per capita is positive. This paper finds sigma convergence of HDI of all states. Only four states showed negative growth of HDI in spite of their rising trends of social sector expenditure. The paper recommended enhancing government expenditure on education and health and to emphasis gender budgeting and FDI inflows.